The Effectiveness of Learning Media Used During Online Learning - Bella Lusiana; Rina Maryanti (Media Pendidikan Gizi dan Kuliner, 2020)
The purpose of this paper is to determine the effectiveness of learning media that can be used during online learning. The Covid-19 pandemic that has hit all parts of the world has affected various sectors, one of which is in the field of education. The teaching and learning process which was originally carried out face to face, has now turned into online learning at home. Learning media is one of the important components in the learning process in the absorption of material to students. By using a qualitative descriptive method, this paper describes, describes, and analyzes the effectiveness of learning media during the online learning period. The data was obtained from distributing questionnaires through Google Forms which were distributed through WhatsApp Group. The results show that WhatsApp Group is considered quite effective in delivering material during online learning by getting a percentage of 45.5%, virtual meeting applications (Zoom and Google Meet) by 27.3%, and Google Classroom by 27.3%.